COVID-19 and Children: Reflections after Three Years - Anna Camporesi; Luigi Vetrugno; Danilo Buonsenso (MDPI AG, 2023)
Three years after the beginning of the COVID-19 pandemic, enough experience has been gained to derive reflections on the impact of SARS-CoV-2 in children [...]